2020
DOI: 10.1002/aoc.5826
|View full text |Cite
|
Sign up to set email alerts
|

1D Azido bridged Cu(II) coordination polymer with 1,3‐oxazolidine ligand as an effective catalyst for green click synthesis of 1,2,3‐triazoles

Abstract: A new 1D azido bridged Cu(II) coordination polymer with 1,3‐oxazolidine based ligand, [Cu(H3L)(μ1,3‐N3)(N3)]n (1), was synthesized and characterized by elemental analysis and spectroscopic methods. The structure of 1 was also determined by single crystal X‐ray analysis which indicated the 1D polymeric chain is generated by end‐to‐end (EE) azide bridge. The obtained compound was employed as catalyst in green click synthesis of β‐hydroxy‐1,2,3‐triazoles from one‐pot three‐component cycloaddition reaction of epox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 83 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Similar to 1 , the Cu(II) ion is five coordinated in 2 and the CuN 2 OBr 2 coordination environment has distorted square pyramidal geometry with τ = 0.064. The Cu–N and Cu–O bond lengths in the equatorial positions of 2 are close to the similar bonds in 1 (see Table 2 ) and are in the normal range reported in similar Cu(II) complexes 68 71 . The Cu–Br1 and Cu–Br2 bond lengths are 2.3602(10) and 2.6607(10) Å, respectively and confirm their coordination to equatorial and axial positions and the presence of Jahn–Teller distortion in the axial direction.…”
Section: Resultssupporting
confidence: 81%
“…Similar to 1 , the Cu(II) ion is five coordinated in 2 and the CuN 2 OBr 2 coordination environment has distorted square pyramidal geometry with τ = 0.064. The Cu–N and Cu–O bond lengths in the equatorial positions of 2 are close to the similar bonds in 1 (see Table 2 ) and are in the normal range reported in similar Cu(II) complexes 68 71 . The Cu–Br1 and Cu–Br2 bond lengths are 2.3602(10) and 2.6607(10) Å, respectively and confirm their coordination to equatorial and axial positions and the presence of Jahn–Teller distortion in the axial direction.…”
Section: Resultssupporting
confidence: 81%
“…This reaction utilized water as the solvent due to its non-toxic properties, cost-effectiveness, and minimal environmental impact. 166 Wang and colleagues presented a MOF that exhibits promising characteristics as a reusable heterogeneous catalyst, capable of efficiently catalyzing click reactions in an aqueous environment, as shown in Table 6, entry (7). 167 Wang et al highlighted a MOF templated Cu(im) 2 derived Cu@N-C catalyst for the one-pot 1,3-dipolar cycloaddition of terminal alkynes, aryl halides and sodium azide in a t-BuOH : H 2 O mixture, yielding 1,4-disubstituted 1,2,3-triazoles with extensive substrate scope and Their study revealed the preparation of diverse 1,2,3-triazoles under solvent-free reaction conditions, achieving good to excellent yields and high selectivity for 1,4-disubstituted 1,2,3-triazoles, as depicted in Table 6, entry (9).…”
Section: Cu-mofs As a Catalystmentioning
confidence: 99%
“…The first use of Cu(II)-azide complex as a catalyst for such reactions was reported by Noshiranzadeh et al [15] Recently, Bikas et al demonstrated the use of a new azido bridged Cu(II) coordination polymer as a catalyst for green click synthesis of 1,2,3-triazoles. [31] Most recent studies on azido-bridged Cu(II) complexes have focused on their synthesis and magnetic properties. [32][33][34] In general, the azido ligand mediates two types of magnetic coupling (antiferromagnetic or ferromagnetic interactions) depending on its coordination modes (μ 1,1 or μ 1,3 ) and on the structural parameters related to the azido bridges (Cu-N distances and Cu-N-Cu angles).…”
Section: Introductionmentioning
confidence: 99%
“…The first use of Cu(II)‐azide complex as a catalyst for such reactions was reported by Noshiranzadeh et al [ 15 ] Recently, Bikas et al demonstrated the use of a new azido bridged Cu(II) coordination polymer as a catalyst for green click synthesis of 1,2,3‐triazoles. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%